AB0341 Metatarsophalangeal joints have more erosions in patients with rheumatoid arthritis. (12th June 2018) - Alagoz, M.; Emlakcioglu, E.; Tunc, A.C.; ,; Kucuk, A.; ,; Gulen, T.; Kocabas, M.; Tunc, R.; ,
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterised by destruction of synovial joints, especially in the hand and feet, leading to severe disability and premature mortality. The erosions seen in RA differentiate it from other rheumatological diseases. Objectives: The aim of the study was to evaluate the relationship between attack frequency and erosions seen in RA. Methods: Forty-four patients according to 2010 ACR/EULAR Classification Criteria for RA were included into the study. Involved joints and number of attacks were recorded. The X-rays of the involved joints were assessed on admission and after 3 months in terms of joint erosion as a blinded manner. Comparison of erosions were calculated by chi-square. Results: Kappa value of intra-observer agreement of reading of x-ray films was 0.68. Erosions were detected in 16 of 44 patients with RA. The Ratios of erosion in joints with more than 10 attacks were different according to involved joints. The ratios of erosions were 10% for metacarpophalangeal (MCP), 8% for proximal interphalangeal (PIP), 0% for knee, 5% for ankle and 69% for metatarsophalangeal (MTP) joints. When compared MTP joints with MCP, PIP and wrist joints, it was seen that the erosion rate was higher in MTP joints than the other joints (p<0, 01). Knee and ankle joints were combined as a single group and compared with MTP joints in terms of erosion. It was seen that the erosions in the MTP joints were significantly higher than the erosions in the knee and ankle joints (p<0, 01). Conclusions: In RA, the erosion ratio of MTP joints was significantly higher than seen in MCP, PIP and wrist joints. On the other hand the erosion rate in knee and ankle joints was rare. These results show us the erosion in MTP joints may not related to mechanical overload. Therefore foot imaging with x-ray may be important in the folllowing of patients with RA. In addition existence of false positive erosions in MTP joints of healthy people should be studied. Disclosure of Interest: None declared